Fakecraft - Paul Christopher Johnson (Journal for the Study of Religion)
The essay defines and explores the dimensions of ‘fakecraft’. It unpacks authenticity in relation to problems of identity, the aura of the original, and commodification. It then shows how notions of authenticity and the fake generate centers and peripheries in the study of religion. The essay explores how traditions of African descent in the Caribbean and Brazil havelong been marginalized in the study of religion as lacking depth or authenticity. The essay then takes up a specific example of fakecraft and its prolific work, namely in early modern Christianity’s process of purification and self-definition through evaluations of demonic possession as ‘real’or ‘fake’, terms that were then applied to the west coast of Africa. In the broadest terms, the article argues that fakecraft–discourses of the real versus the merely mimetic–is basic to religion-making.